Twisted innocence - Blackstock, Terri, 1957- (Blackstock, Terri, 1957- Moonlighters series, 2015)
Holly Cramer has stumbled through most of her adult life as a partygirl, but she longs to live a more stable life for her daughter, Lily. When police show up to question her about the whereabouts of Lily's father, Creed Kershaw, a person of interest in a drug-related murder case, she is determined to keep him out of their lives and turn him over to police. But her bravado backfires when he turns the tables and takes her and Lily hostage. As desperate hours tick by, Holly realizes his connection to Leonard Miller the man who has gunned down several members of her family. Creed claims he's innocent and that Miller is after him too. Dangers old and new threaten Holly and her baby, and lives are demanded as sacrifices for love. Through a complex web of mistakes and regret, redemption is the one hope Holly has left to hold on to.